Securing livelihood through ber-based cropping system - Verma, Ajay Kumar; Saroj, P L (Indian Horticulture, 2019)
Livelihood security in hot arid region is a major challenge due to fundamental environmental constraints such as scanty and erratic rainfall, recurrent drought, extreme temperatures, high wind velocity and poor soil conditions. Monocropping is often risky with meagre crop yields and unstable income from existing crop is hardly sufficient to sustain the farmers’ family. Therefore, to mitigate the risk and uncertainty of the income from conventional cropping, there is a need to enhance the productivity through integration of various components in the production programme that yield regular and evenly distributed income. Horticulture based farming system has a vital scope in diversification, productivity enhancement and employment generation on long term basis. Ber-based cropping system offers considerable scope for increasing production and productivity per unit area, time and inputs by more efficient utilization of resources like sunlight, soil, water and labour. This system is ideally suited and economically viable for small and marginal famers of hot arid zone.